Relações de tradução: SAY/DIZER em corpora de textos ficcionais - Silvana Maria de Jesus (2008)
This dissertation reports on a study developed at LETRA - Laboratory for Experimentation in Translation, Faculdade de Letras, UFMG. Building on Catford's (1965) foundational work on translation and Matthiessen's (2007) proposal of systemic functional translation studies of multilingual production and translation, it presents three different and complementary approaches to examine equivalence relations between two verbs in the pair English-Portuguese, SAY/DIZER. Equivalence is looked at from an empirical perspective drawing on data gathered from translated and non-translated fiction in both languages and in both translation directions. Using the methodology of corpus linguistics for quantitative data analysis (WordSmith Tools and SPSS - Statistical Package for the Social Sciences) and a combined corpus (comparable and parallel) compiled to that end, equivalence relations are studied from a three dimensional perspective. The first approach analyses the functions of SAY/DIZER in non-translated texts, describing functional meanings realized by these verbs, according to the metafunctional theory in systemic functional linguistics (Halliday and Matthiessen, 2004). Commonalities and differences are considered as the first step in order to look at equivalence relations. The second approach investigates the originals and their translations to search and account for possible equivalents as well as their probabilities of occurrence. Both unconditioned and conditioned probabilities of equivalence, as proposed by Catford (1965), are examined. The third approach analyses the use of SAY/DIZER in translated texts, comparing patterns in translated and non-translated texts in order to examine how the relations among the texts condition the different patterns found. Occurrences in the original texts that were translated as SAY/DIZER are also examined in order to account for possible equivalents. Results point to different patterns of these verbs, relating to their functions and to equivalence relations.